THU0557 Haemophagosytic Limphohistiosytosis (HLH) in Adults. Diseases Triggers, Course, Treatment and Pronostic Factors. Differences Between Patients with Macrophage Activation Syndrome (MAS) and Other Causes of Secundary Heamophagosytic Limphohistiosytosis (SHLH). report Of Thirty-Two Cases. (9th June 2015) - Komsalova, L.Y.; Lopez, L.M.
Abstract : Background: The secondary hemophagocytic lymphocytosis syndrome (SLHS) is a rare fatal diseasewithout specific treatment. In the present study 32 cases are reported on with SLHS diagnosed by bone marrow biopsy in the period from 1995 to 2013. Objectives: Comparison between patients with Macrophage activation syndrome (MAS) and other causes of secondary hemophagocytic lymphohistiocytosis (HLH). Disease triggers, causes, course, treatment and pronostic factors. Methods: Outcomes analysed were overall survival (from the time of patient's hospitalization until the patient's death) and due to fact that the majorities of the demises were performed in the first 5 weeks, two another variables were chosen: extremely severe disease (demises in the first month) and severe disease (demises in the first two months). The variable age was assessed by T Student. Chi square and cross tabulation were used for analyze categorical variables. Statistical significance was set at P<0.05. Associations were expressed using Odds ratios (ORs) with 95% confidence interval (95% CI). Results: The average age of patients was 44.50 years (range 14-78 years), with a ratio 1.13/1 men/women. The associated diseases were: autoimmune illness - 10 (31.3%), Kidney or Liver transplant - 9 (28.1%), hematological disease - 5 (15.6%), infection -5 (15.6%) and solid cancer - 3 (9.4%) patients. The most frequent clinical manifestations were a temperature over 38.5° 32 (100%) patients, splenomegaly, 23 (71.9%) and severe hepatopathy 19 (59.4%). The most prominent analytical data was: anemia less than 8.5 mg/dl in 18 (56.3%) of the patients, neutropenia less than 500 in 13 (40.6%) and thrombocytopenia less than 35, 000 in 15 (46.9%) of them. The prognostic factors associated with mortality were: age>47 years (p<0.013), the associated cancer (p<0.049), the previous treatment with glucocorticoid (p<0.011), previous use of mycophenolate mofetil (p<0.032), the presence of anemia (p<0.03), bicytopenia (p<0.005), severe pancititopenia (p<0.020) and affectation of vital organs such as the lung (p<0.017). Significant association was found between the severity of the disease and anemia (p<0.001), neutropenia (p<0.036) thrombocytopenia (p<0.020) and pancytopenia (p<0.020) severe, hypofibrinogenemia lower than 100 mg/dl, the associated cancer and the coincident infection. The non instauration of specific treatment is associated to worse prognosis and higher probability to develop severe illness (p<0.049), for which close monitoring is necessary and more aggressive treatment from the clinical suspicion. Conclusions: The main differences reside in the better prognosis of the patients with MAS and the lesser proportion associated with severe illness (p<0.005). The presence of autoimmune disease seems to act as a trigger factor per se, and the infection does not appear to play an important role in patients with MAS (p<0.018). The Ferritin levels higher than 5, 000 were more typical for patients with previous autoimmune disease MAS (p<0.046). Acknowledgements: All my colleages. Disclosure of Interest: None declared